The Madrasah Principal's Strategy for Improving the Performance Quality of Honorary Teachers at MTs Al-Ikhlas Moubang, Parigi Moutong Regency - ISMAIL (Journal of Education and Teaching Learning, 2026)
This research was motivated by the importance of teacher performance quality.  The quality of honorary teachers is a crucial pillar for the continuity of education in private madrasah. However, honorary teachers often face challenges such as low welfare and limited facilities. This condition demands an extraordinary leadership role to maintain academic stability. This research employed a qualitative approach with a descriptive method. The data analysis techniques included data reduction, data presentation, and conclusion. The validity of the data was tested through triangulation techniques. The findings of this research showed that the Madrasah principal’s strategy was based on a leading by example model and participatory supervision through routine weekly evaluations. However, several challenges were still found, including low honoraria, limited digital facilities, and geographical barriers. The implications of this research confirm that exemplary leadership can be an alternative solution to addressing the material limitations experienced by honorary teachers in educational institutions. This research also illustrates that emotional recognition and the involvement of honorary teachers in a humanistic evaluation process can significantly enhance their loyalty and work dedication